(3GdCZPjI hGdCTQHI ddCUMGAs - (3eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO, GdfLjH GdSeQbfOj , J (B619 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdjef Ef Gddg JYGdi deG Ndb fhY GdEfSGf CYOd eRLkG ef LejY GdMjhGfGJ hLH Cf Jchf CZPjJge eJaffI , cKjQI GdCUfGa eNJdaI GdWHGFY s
(3BNQgG (B:s
(3ajfHZi Cf jchf GSJYeGdgG hGdaRY EdjgG YfO GdMGLI Edi JbhjI GdbdH hGdOeGZ , hYfO GdVYa hGYTi CcKQ hCTO ef GSJYeGd GdQhGFM GdWHjI hGddg GYde s
(3GdbSe GdQGHY ef GdfLjHjGJs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B280 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B31s
Keywords: (3GdWHs